Survival in borderline resectable and locally advanced pancreatic cancer is determined by the duration and response of neoadjuvant therapy. Issue 10 (October 2021) - Wijetunga, Asanka R.; Chua, Terence C.; Nahm, Christopher B.; Pavlakis, Nick; Clarke, Stephen; Chan, David L.; Diakos, Connie; Maloney, Sarah; Ashrafi-Zadeh, Amir; Kneebone, Andrew; Hruby, George; Jamieson, Nigel B.; et al.
Abstract: Background: Pancreatic cancer is the 8th commonest cancer and the 5th commonest cause of cancer-related death in Australia, with a 9% average 5-year survival. This study aims to investigate the effects of neoadjuvant treatment on overall survival (OS) and recurrence-free survival (RFS) in borderline resectable (BRPC) and locally advanced (LAPC) pancreatic adenocarcinoma followed by curative resection. Materials and methods: Prospectively-collected demographic, medical, surgical and pathological data of patients with BRPC and LAPC treated with both neoadjuvant therapy (NAT) and surgery at a single tertiary referral centre in Australia were reviewed and analysed. Results: Between 2012 and 2018, 60 patients, 34 with BRPC and 26 with LAPC, were treated with NAT followed by curative resection. The commonest neoadjuvant chemotherapy regimens were Gemcitabine + Abraxane (51.7%) and FOLFIRINOX (35.0%), with 48.3% of patients additionally receiving neoadjuvant radiotherapy. Median RFS was 30 months and median OS was 35 months. On multivariable analysis, inferior OS was predicted by enlarged loco-regional lymph nodes on initial computed tomography (p = 0.032), larger tumour size post-NAT (p = 0.006) and Common Terminology Criteria for Adverse Events post-NAT toxicity greater than grade 2 (p = 0.015). LAPC patients received more neoadjuvant chemotherapy (p = 0.008) and radiotherapy (p = 0.021) than BRPC and achieved a superior pathological response (p = 0.010). Conclusion: Patients who respond to NAT likely have a favourable disease biology and will progress well following resection. It is these patients who should be selected for more aggressive upfront management, and those with resistant disease should be spared from high-risk surgery.